2015
DOI: 10.1111/ijcp.12676
|View full text |Cite
|
Sign up to set email alerts
|

Association of gastrointestinal events and osteoporosis treatment initiation in newly diagnosed osteoporotic Israeli women

Abstract: SummaryBackgroundThe objective was to examine the association of gastrointestinal (GI) events and osteoporosis treatment initiation patterns among postmenopausal women following an osteoporosis diagnosis from an Israeli health plan.MethodsThis retrospective analysis of claims records included women aged ≥ 55 years with ≥ 1 osteoporosis diagnosis (date of first diagnosis was index date). Osteoporosis treatment initiation was defined as use of osteoporosis therapy (oral bisphosphonates or other) during 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…MHS is a fully computerized organization. Information including patient records, billing systems, pharmaceutical dispensations, and chronic disease registries is housed in the organization’s central electronic warehouse DATA BASE These automated datasets have been previously described at length in previous studies [ 9 12 ]. During the physician/nurse patient encounter, all of the information collected is recorded electronically in either coded or free text fields.…”
Section: Introductionmentioning
confidence: 99%
“…MHS is a fully computerized organization. Information including patient records, billing systems, pharmaceutical dispensations, and chronic disease registries is housed in the organization’s central electronic warehouse DATA BASE These automated datasets have been previously described at length in previous studies [ 9 12 ]. During the physician/nurse patient encounter, all of the information collected is recorded electronically in either coded or free text fields.…”
Section: Introductionmentioning
confidence: 99%
“…This is not without precedent: a Swedish study using data from 2001-2004 found that those with dementia were less likely to receive OP medications than those without dementia, after adjusting for other factors 35 . The potential for side-effects has been cited as a barrier to OP treatment 26 , and the occurrence of GI events, specifically, has been shown to reduce the likelihood of receiving any OP treatment 20,36 , as well as the likelihood of being treated with a BP versus a non-BP 25 . In the current study, baseline GI events were associated with increased odds of OP treatment during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study sample represented older women, the association between post-diagnosis GI events and reduced odds of treatment initiation that we observed complement previous findings in younger patients. In a study of Israeli women (mean age 65 years), which used methodology comparable to ours, Yu and colleagues observed that a post-diagnosis GI event reduced the odds of treatment initiation by 85 % [ 33 ]. Among US women (mean age 66 years), post-diagnosis GI events were associated with 75 % lower likelihood of treatment initiation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%